Analysis of fetal heart rate asymmetry before and after 35 weeks of gestation. (August 2015) - Karmakar, Chandan; Kimura, Yoshitaka; Palaniswami, Marimuthu; Khandoker, Ahsan
Highlights: We examine the presence and change of heart rate asymmetry (HRA) with fetus growth. Fetal heart rate asymmetry (fHRA) increases with increasing gestational ages. fHRA is closely related to development of Autonomic Nervous System (ANS) Multi-lag fHRA is better marker to separate early from late fetuses than single lag. Abstract: In this study, we have investigated the evidence of fetal heart rate asymmetry and how the fetal heart rate asymmetry changes before and after 35 weeks of gestation. Noninvasive fetal electrocardiogram (fECG) signals from 45 pregnant women at the gestational age from16 to 41 weeks with normal single pregnancies were analysed. A nonlinear parameter called heart rate asymmetry (HRA) index that measures time asymmetry of RR interval time-series signal was used to understand the changes of HRA in early and late fetus groups. Results indicate that fetal HRA measured by Porta's Index (PI) consistently increases after 35 weeks gestation compared to foetus before 32 weeks of gestation. It might be due to significant changes of sympatho-vagal balance towards delivery with more sympathetic surge. On the other hand, Guzik's Index (GI) showed a mixed effect i.e., increases at lower lags and decreases at higher lags. Finally, fHRA could potentially help identify normal and the pathological autonomic nervous system development.